In Bureaucrats We Trust? Good Governance and Trust in Civil Servants - Morelock, Andrew L. (Public administration quarterly, 2021)
While a sizeable literature exists that examines individuals’ trust in government, far less attention has been paid to analyzing trusting attitudes in civil servants – the agents of government with whom citizens have the most contact and interaction. Previous studies have found a noticeable link between public sector performance and the level of trust citizens have in public institutions. However, questions remain as to whether it is the outcomes that the public sector produces or otherwise the process that is used that most influences trusting attitudes. The data used in the analysis comes from the 2016 International Social Survey Programme (ISSP) module “Role of Government V.” Data from national samples drawn from 23 OECD countries are examined using multilevel logistic regression. The results indicate that individuals living in countries characterized by better governance indicators are more trusting of civil servants than those in countries where procedural performance is poorer.